Predictive value of CD4 cell count nadir on long-term mortality in HIV-positive patients in Uganda - Bray, Sarah; Gedeon, Jillian; Hadi, Ahsan ard J Mills; Kotb, Ahmed; Rahman, Tarun; Sarwar, Elaha; Savelyeva, Anna; Sévigny, Marika; Bakanda, Celestin; Birungi, Josephine; Chan, Keith; Yaya, Sanni; et al. (HIV/AIDS – Research and Palliative Care, 2012)
Although international guidelines recommend initiating antiretroviral therapy (ART) when a patient’s CD4 cell count is #350 cells/μL, most patients in resource-limited settings present with much lower CD4 cell counts. The lowest level that their CD4 cell count reaches, the nadir, may have long-term consequences in terms of mortality. We examined this health state in a large cohort of HIV+ patients in Uganda. Design: This was an observational study of HIV patients in Uganda aged 14 years or older, who were enrolled in 10 major clinics across Uganda. Methods: We assessed the CD4 nadir of patients, using their CD4 cell count at initiation of ART, stratified into categories (,50, 50–99, 100–149, 150–249, 250+ cells/μL). We constructed Kaplan–Meier curves to assess the differences in survivorship for patients left-censored at 1 year and 2 years after treatment initiation. We used Cox proportional hazards regression to model the associations between CD4 nadir and mortality. We adjusted mortality for loss-to-follow-up. Results: Of 22,315 patients, 20,129 patients had greater than 1 year of treatment follow-up. Among these patients, 327 (1.6%) died and 444 (2.2%) were lost to follow-up. After left-censoring at one year, relative to lowest CD4 strata, patients with higher CD4 counts had significantly lower rates of mortality (CD4 150–249, hazard ratio [HR] 0.60, 95% confidence interval [CI]: 0.45–0.82, P = 0.001; 250+, HR 0.66, 95% CI, 0.44–1.00, P = −0.05). Male sex, older age, and duration of time on ART were independently associated with mortality. When left-censoring at 2 years, CD4 nadir was no longer statistically significantly associated with mortality. Conclusion: After surviving for 1 year on ART, a CD4 nadir was strongly predictive of longer-term mortality among patients in Uganda. This should argue for efforts to increase engagement with patients to ensure a higher CD4 nadir at initiation of treatment.
Keywords: Antiretroviral therapy; ART; CD4; Prognosis; Sub-Saharan Africa